2011
DOI: 10.1186/1471-244x-11-101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of asenapine on depressive symptoms in patients with bipolar I disorder experiencing acute manic or mixed episodes: a post hoc analysis of two 3-week clinical trials

Abstract: BackgroundAsenapine demonstrated superiority over placebo for mania in bipolar I disorder patients experiencing acute current manic or mixed episodes in 2 randomized, placebo-and olanzapine-controlled trials. We report the results of exploratory pooled post hoc analyses from these trials evaluating asenapine's effects on depressive symptoms in patients from these trials with significant baseline depressive symptoms.MethodsIn the original trials (A7501004 [NCT00159744], A7501005 [NCT00159796]), 977 patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 23 publications
2
48
1
Order By: Relevance
“…These trends are inconsistent with results of other two clinical trials of subjects with bipolar disorder [52], where asenapine was found superior to olanzapine in improving depressive symptoms during manic or mixed episodes. A possible reason for this inconsistency may be that, whilst in our sample HAM-D scores at baseline were rather low (with a mean lower than 13) as patients with concomitant major depression had been excluded, in the other two studies of bipolar disorder patients [52] depressive symptoms were rated as "clinically relevant".…”
Section: Discussioncontrasting
confidence: 89%
“…These trends are inconsistent with results of other two clinical trials of subjects with bipolar disorder [52], where asenapine was found superior to olanzapine in improving depressive symptoms during manic or mixed episodes. A possible reason for this inconsistency may be that, whilst in our sample HAM-D scores at baseline were rather low (with a mean lower than 13) as patients with concomitant major depression had been excluded, in the other two studies of bipolar disorder patients [52] depressive symptoms were rated as "clinically relevant".…”
Section: Discussioncontrasting
confidence: 89%
“…In these studies, asenapine but not olanzapine was reported to reduce 'clinically relevant depressive symptoms' in the frame of a manic/mixed episode [483].…”
Section: Methodsmentioning
confidence: 98%
“…A post-hoc analysis of two asenapine RCTs in patients with manic or mixed episodes demonstrated statistically significant decreases in depression scores with asenapine versus placebo in patients with severe baseline depressive symptoms (n = 604); differences between the active comparator olanzapine and placebo were not significant, which makes the interpretation of these results more difficult as it raises the possibility of a negative study (80). Pharmacological management of acute bipolar depressive episodes should follow the algorithm outlined in Figure 4.1 (1-3).…”
Section: Mixed Statesmentioning
confidence: 99%